On-Ground Testing of Dual-Sided Release Mechanism of TianQin Test Mass Using a Pendulum - Ji Wang; Diwen Shi; Chao Xue; Biao Yang; Bingwei Cai; Jie Chang; Zefan Zhou; Wenhai Tan; Shanqing Yang (Sensors)
The high-precision gravitational reference sensor, which hosts a heavy test mass (TM) surrounded by electrodes with a relatively large gap, is crucial in all high-sensitivity drag-free sensors. Consequently, a dedicated locking mechanism is needed to securely hold the TM during the launch phase. After reaching the intended orbit, the TM is released to a free-falling state and subsequently captured by electrostatic actuation, which demands that the transferred momentum and angular momentum to the TM do not exceed <semantics>10−5<mspace width="4pt"></mspace>kgm/s</semantics> and <semantics>10−7<mspace width="4pt"></mspace>kgm2/s</semantics>, respectively. This paper introduces a three-level structural design of the locking-and-release mechanism. In order to investigate the release requirement, a pendulum system has been developed for on-ground testing. The mock-up of the TM is entirely consistent with the size and mass of TianQin TM, and the dual-sided release tips constrain the TM and then rapidly retract simultaneously, after which the transferred momentum and angular momentum are estimated from the free oscillations as <semantics>0.38(21)×10−5<mspace width="4pt"></mspace>kgm/s</semantics> and <semantics>0.15(14)×10−7<mspace width="4pt"></mspace>kgm2/s</semantics> with a preload force of 0.3 N. This proposes a feasible scheme for validating the release mechanism conducting impulse testing for the TianQin project.